Severe acute respiratory syndrome coronaviruses with mutations in the E protein are attenuated and promising vaccine candidates - Regla-Nava, Jose Angel; Nieto-Torres, Jose Luis; Jimenez-Guardeño, Jose Manuel; Fernandez-Delgado, Raul; Fett, Craig; Castaño-Rodriguez, Carlos; Perlman, Stanley; Enjuanes, Luis; DeDiego, Marta L. (ASM Journals, 2015)
Severe acute respiratory syndrome coronavirus (SARS-CoV) causes a respiratory disease with a mortality rate of 10%. A mouse-adapted SARS-CoV (SARS-CoV-MA15) lacking the envelope (E) protein (rSARS-CoV-MA15-ΔE) is attenuated in vivo. To identify E protein regions and host responses that contribute to rSARS-CoV-MA15-ΔE attenuation, several mutants (rSARS-CoV-MA15-E*) containing point mutations or deletions in the amino-terminal or the carboxy-terminal regions of the E protein were generated. Amino acid substitutions in the amino terminus, or deletion of regions in the internal carboxy-terminal region of E protein, led to virus attenuation. Attenuated viruses induced minimal lung injury, diminished limited neutrophil influx, and increased CD4(+) and CD8(+) T cell counts in the lungs of BALB/c mice, compared to mice infected with the wild-type virus. To analyze the host responses leading to rSARS-CoV-MA15-E* attenuation, differences in gene expression elicited by the native and mutant viruses in the lungs of infected mice were determined. Expression levels of a large number of proinflammatory cytokines associated with lung injury were reduced in the lungs of rSARS-CoV-MA15-E*-infected mice, whereas the levels of anti-inflammatory cytokines were increased, both at the mRNA and protein levels. These results suggested that the reduction in lung inflammation together with a more robust antiviral T cell response contributed to rSARS-CoV-MA15-E* attenuation. The attenuated viruses completely protected mice against challenge with the lethal parental virus, indicating that these viruses are promising vaccine candidates.
Keywords: Virus; Virology; SARS-CoV